Exercise and Omentin: Their Role in the Crosstalk Between Muscle and Adipose Tissues in Type 2 Diabetes Mellitus Rat Models - Castro, Cynthia Aparecida de; Silva, Karina Ana da; Rocha, Marina Campos; Sene-Fiorese, Marcela; Nonaka, Keico Okino; Malavazi, Iran; Anibal, Fernanda de Freitas; Duarte, Ana Cláudia Garcia de Oliveira (Frontiers in Physiology, 2019)
This study aims to analyse the effects of resisted, aerobic and combined exercises on omentin levels in visceral adipose tissue and muscle of rats with experimental diabetes to verify whether these adipokines are related to the glucose pathway and inflammation process in this model. Male Wistar rats received a high-fat diet for 4 weeks and a low dose of streptozotocin (35mg/kg) to induce experimental diabetes. After inducing diabetes, the animals were divided into 4 experimental groups (n=10): diabetic control (C); resistance training (RT); aerobic training (AT) and combined training (CT). The groups were exercised for 12 weeks, 3 times/week, where: RT means the stair climbing protocol until exhaustion; AT is the 30 min/day reaching 20m/min protocol, and CT is the combination of resistance training and aerobic training. The AT group showed reduced retroperitoneal and mesenteric adipose tissue and abdominal fat deposits. Our study also showed a possible control of blood glucose, as well as decreased Interleukin 6 (IL-6) and C-reactive protein, increased circulating adiponectin and increased omentin in visceral adipose tissue . In addition, the AT group affected the glucose pathway by stimulating phosphorylation of Akt in muscle tissue. Omentin also showed a strong positive correlation with adiponectin and a moderate negative correlation with IL-6. Thus, our findings indicated that omentin in type 2 diabetes is changed by aerobic training. Furthermore, increased omentin levels had a close association with the glucose pathway by stimulating phosphorylation of Akt in muscle tissue and with IL-6 in serum, suggesting that omentin is likely to have anti-inflammatory/protective action in experimental diabetes.